МЕТОДИКА НАЛОГОВОГО ПЛАНИРОВАНИЯ ПРИБЫЛИ ОРГАНИЗАЦИИ НА БАЗЕ СТАТИСТИЧЕСКОЙ МОДЕЛИ БУХГАЛТЕРСКОГО УЧЕТА - Каипова, Г С (Journal of Economic Research & Business Administration, 2015)
Article is devoted elements of tax planning and forecasting of financial result of activity of the organisation. In two types of the offered models the basic criterion of practical suitability of economic actions of the organisations is the net profit.